Effects of Propofol, Low and High Doses of Remimazolam on Hemodynamic and Inflammatory Response in Laparoscopic Surgery [Response to Letter] - Deng W; Zeng Z; Liu Q; Deng J; Wang L; Li H; Zhang Y (Dove Medical Press, 2024)
Wenguang Deng, Zhiming Zeng, Qingyan Liu, Jingjing Deng, Liyu Wang, Hui Li, Yuenong Zhang The Anesthesiology Surgery Center of The Third Affiliated Hospital of Sun Yat-sen University-Yuedong Hospital, Guangdong, People’s Republic of ChinaCorrespondence: Yuenong Zhang, Email 36856665@qq.com